Efectos del tabaquismo pasivo asociado con el ejercicio físico en los músculos esqueléticos de ratas durante la gestación y lactancia - Valsoni, Bruna Corral Garcia [UNESP]; Bonfim, Mariana Rotta [UNESP]; Camargo, Regina Celi Trindade [UNESP]; de Abreu, Luiz Carlos; Souza, Dorotéia Rossi Silva; Camargo Filho, José Carlos Silva [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2015)
The objective of this study was to analyze the effects of passive smoking, in soleus and gastrocnemius muscles associated with physical exercise by swimming during pregnancy and lactation of rats. Twenty-four rats were divided: GF (exposed to cigarette smoke), GC (control), GFN (underwent to the swimming program and exposed to cigarette smoke) and GN (underwent to the swimming program). On the first day of pregnancy procedure of exposure to cigarette smoke began, consisting in 30 minutes twice a day for six weeks. During the same period the swimming program began, which lasted 60 min every day untilthe 21st day of lactation. Soleus and gastrocnemius muscles, were obtained for histological, histochemical, morphometric analysis and fiber profiling. In histology, the groups GF and GFN showed infiltrations, necrotic and phagocytized fibers, centralized nuclei, splittings and coiling; in GN changes were observed due to exercise adaptations, infiltrations, sarcolemal lesion, polymorphic, atrophic and angular fibers. In the histochemical analysis of the groups GF and GFN there was enzymatic activity and amorphous formazan aggregates in subsarcolemmal positions, however in GN the same changes were found in lower frequency and intensity. In regard to the measure of the cross-section of muscle fibers there weren’t significant differences among the groups, as well as, in the frequency of types of fibers of the gastrocnemius. It is concluded that aerobic exercise is not enough to impede morphological and histochemical changes caused in an animal model of pregnant and lactating associated with smoking, and the stress not influence the types and size of muscle fibers.
Effects of passive smoking associated with physical exercise in the skeletal muscles of rats during pregnancy and lactation
Keywords: Lactation; Passive smoking; Physical exercise; Pregnancy; Skeletal muscle